Estimate of the prevalence of depression among older people in Africa: a systematic review and meta-analysis. (19th May 2022) - Bedaso, Asres; Mekonnen, Nibretie; Duko, Bereket
Abstract: Objective: The current systematic review and meta-analysis aimed to estimate the pooled prevalence of depression among elderly people in Africa. Method: We have searched CINAHIL, PubMed, SCOPUS and Psych-INFO databases to identify important observational studies which reported the prevalence of depression among the elderly. We used a random-effects model due to reported heterogeneity among the included studies. The publication bias was examined by using Egger's test, visual inspection of the symmetry in funnel plots and adjusted using Duval and Tweedie's Trim and Fill analysis. We have meta-analysed the pooled estimates of depression from primary studies by adjusting for publication bias. We used Cochran's Q and the I 2 -tests to measure heterogeneity across the studies. Result: A total of 23 studies conducted in Africa were included in the current systematic review and meta-analysis, representing a total of 14, 350 elderly population. The pooled prevalence of depression among elderly people in Africa was estimated to be 26.3% (95% CI; 22.2, 30.4%). The estimated pooled prevalence of depression among the elderly in Africa was much higher (43.1%) in studies that used a screening tool to measure depression when compared to studies that used a diagnostic tool (24.2%). Also, the prevalence of depression among female elderly participant (43.10%) was higher than that of male elderly participant (30.90%). Conclusion: One in five elderly population in Africa were depressed, which poses serious health concerns. Timely and targeted screening of depression among the elderly and evidence-based interventions were highly recommended.